Um olhar para a educação de usuários do Sistema Integrado de Bibliotecas da Universidade Federal de Pernambuco - Santiago, Sandra Maria Neri (2010)
User education is a segment of real value, in view of that, users acquire new behaviors in using the library and establish interaction with the information system. This research aims to examine the existing user education practices in the Libraries that comprise the SIB/UFPE. This is a case study, with an exploratory and descriptive character. The methodology adopted covers a desk research, a bibliographical research and a field research, the latter being composed of two steps. The universe is composed of 12 librarians with a direction and coordination position in the Libraries of SIB/UFPE and 42 students from the 7th semester of Librarianship. The random sample is directed only to the students category, which represents 95% of the universe. We used as instruments of data collection the questionnaires, programs and reports relating to the user education activities developed by the libraries. To analyze the data, we used a qualitative and quantitative approach, prioritizing some elements of content analysis. In the first step of the research we identified that the SIB/UFPE is composed of 12 University Libraries: 11 located in academic centers, and one without link with any center. The libraries were created in different years, 1830, 1968, 1974, 1976, 1983, 1986, 1988, 1992, 1997, 1994 and 2006. The numbers of registered users are respectively from the Libraries: CAV with a total of 1,084, CCJ 1,707, CTG 2,963, Reitor Ednaldo Bastos Library 4,446, and the Yves Marie Gilles de Maupeou Library 2,499, totaling 12,699 users. The staff is composed of a number of 257, being 72 librarians, 80 administrative assistants, 105 fellows and 10 other professionals. The Libraries of SIB/UFPE conduct user education activities of both formal and informal type. For the evaluation of the activities carried out, the instrument used is the questionnaire. The main difficulty found for holding the activities was the institutional barrier. The possibilities of accomplishment were understood from the perspective that the respondents are aware of the importance of seeking improvements in the quality and effectiveness of the activities undertaken on behalf of its users. In the second step of the research, the results show that most of the users are female, aged 21 to 24 years, student as occupation, family income between 1 and 3 minimum wages, considered actual users of the libraries. The users do not have difficulties regarding the use of the informational products and services offered by the libraries, but it is necessary to consider the answers to other questions where the interpersonal barrier was revealed. The study reveals that the user education practices in the Libraries of SIB/UFPE are geared to informality, requiring adjustments to achieve the informational desires of its users; ratifies the need to implement a user education policy, to guide the service; and presents some guidelines for establishing such policy. We conclude therefore that the findings of this research corroborate the literature of the area, because the education of users within the University Libraries is considered essential, necessary and of great relevance.